MANAJEMEN KINERJA GURU DI MAN 1 BATUBARA KECAMATAN LIMAPULUH KABUPATEN BATUBARA - Capah, Fahrul Rozi; Chaniago, Nasrul Syakur (Dharmas Education Journal (DE_Journal), 2023)
Performance is the level of success of a person or group of people in carrying out their duties and responsibilities as well as the ability to achieve the goals and standards that have been set. So in this case the teacher must have a number of competencies or master a number of knowledge, attitudes, and skills related to his field of work. A teacher's performance is a combination of abilities, efforts, and opportunities that can be assessed from the results of his work. The teacher has the most important responsibility, namely how to condition a fun learning environment so that it can arouse students' curiosity. This study uses a qualitative descriptive research approach with the research subjects being the entire board of teachers at MAN 1 Batubara. The techniques used in this research are interviews, observation and documentation. The results of the study show that teachers at MAN 1 Batubara use visual online learning media in their teaching and learning process. As well as work evaluations are still often carried out to improve teacher performance.